Cognitive Performances: The Role of Digit Ratio (D2:D4) With a Protective Factor for Anxiety - Rinella, Sergio; Massimino, Simona; Sorbello, Alessia; Perciavalle, Vincenzo; Coco, Marinella (Frontiers in Neuroergonomics, 2022)
The aim of this study was to identify a possible correlation between the D2:D4 Ratio and State and/or Trait Anxiety in adult healthy subjects and, if so, whether it exists any difference between men and women. In addition, we also wanted to observe whether there is a relationship between participants' age and State and/or Trait Anxiety. The research involved 125 subjects of both sex, who were calculated the D2:D4 ratio and were administered the self-assessment questionnaire STAI-Y (State-Trait Anxiety Inventory). Results shows that there are positive significant correlations between D2:D4 ratio and score at State Anxiety as well as Trait Anxiety, in the total sample. However, if men are examined separately from women, it can be observed that only men have a statistically significant relationship between D2:D4 ratios and State Anxiety as well as Trait Anxiety. Moreover, about possible relations between the age of participants and State as well as Trait Anxiety, a significant negative relation was observed, without differences between men and women. However, only subjects with a D2:D4 Ratio ≥1, without differences between men and women, showed a statistically significant negative linear correlation between their age and their State as well as Trait Anxiety. The present data allow us to conclude that a low D2:D4 ratio (<1) represents a protective factor against Anxiety in both men and women and that this protection seems likely to act throughout life.